Anti-inflammatory action of 2-carbomethoxy-2, 3-epoxy-3-prenyl-1, 4-naphthoquinone (CMEP-NQ) suppresses both the MyD88-dependent and TRIF-dependent pathways of TLR4 signaling in LPS-stimulated RAW264.7 cells. (9th June 2017) - Ju Woo, Hyun; Jun, Do Youn; Lee, Ji Young; Park, Hae Sun; Woo, Mi Hee; Park, Sook Jahr; Kim, Sang Chan; Yang, Chae Ha; Kim, Young Ho
Abstract: Ethnopharmacological relevance: The roots of Rubia cordifolia L. have been widely used as a traditional herbal medicine in Northeast Asia for treating inflammatory diseases. Aim of the study: To elucidate the anti-inflammatory mechanism of 2-carbomethoxy-2, 3-epoxy-3- prenyl-1, 4-naphthoquinone (CMEP-NQ), purified from the roots of R. cordifolia L. as the major anti-inflammatory component, in LPS-treated RAW264.7 murine macrophage cells. Materials and methods: Anti-inflammatory activity of CMEP-NQ was investigated in LPS-treated RAW264.7 cells by measuring the levels of NO, PGE2, and cytokines (IL1β, IL-6, TNF-α) in the culture supernatants and the TLR4-mediated intracellular events including association of MyD88 with IRAK1, activation of IRAK1, TAK1, MAPKs, NF-κB/AP-1, and IRF3, and generation of ROS. Results: Pretreatment of RAW264.7 cells with CMEP-NQ reduced LPS-induced production of NO and PGE2 by suppressing iNOS and COX-2 gene expression. CMEP-NQ also reduced the secretion of IL-1β, IL-6, and TNF-α by down-regulating mRNA levels. Under these conditions, TLR4-mediated MyD88-dependent events were inhibited by CMEP-NQ, including the association of MyD88 with IRAK1, phosphorylation of IRAK1, TAK1, and MAPKs (ERK, JNK and p38 MAPK), and activation of NF-κB and AP-1. As TRIF-dependent events of TLR4 signaling, phosphorylation of IRF3 and induction of iNOS protein expression were also inhibited by CMEP-NQ. However, the binding of FITC-conjugated LPS to cell surface TLR4 was not affected by CMEP-NQ. Following LPS stimulation, intracellular ROS production was first detected by DCFH-DA staining at 1 h; then it continuously increased until 16 h. Although CMEP-NQ failed to exhibit DPPH radical- or ABTS radical-scavenging activity in vitro, LPS-induced ROS production in RAW264.7 cells was more efficiently blocked by CMEP-NQ than by NAC. Conclusions: These results demonstrate that the suppressive effect of CMEP-NQ on LPS-induced inflammatory responses in RAW264.7 cells was mainly exerted via its inhibition of TLR4-mediated proximal events, such as MyD88-dependent NF-κB/AP-1 activation and ROS production, and TRIF-dependent IRF3 activation. Graphical abstract: